2013
DOI: 10.1017/thg.2012.153
|View full text |Cite
|
Sign up to set email alerts
|

Twin Pregnancies: Evaluation of Major Depression, Stress, and Social Support

Abstract: Background: Twin pregnancies are at increased physiological and psychosocial risks. Objective: To investigate the prevalence of major depression in twin pregnancies and correlate with stress and social support. Method: The study included 51 pregnant women under specialized prenatal care who were evaluated by a Portuguese version of the semi-structured questionnaire Primary Care Evaluation of Mental Disorders (PRIME-MD) for Major Depression, and the Prenatal Psychosocial Profile (PPP) for evaluation of stress a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 31 publications
0
15
0
1
Order By: Relevance
“…Systematic review shows that that parents of multiples experience heightened symptoms of depression, anxiety, and parental stress that parents of singletons. Major depression occurs in one-third of pregnant women expecting twins and is associated with higher levels of stress and lack of social support [39]. The couple's relationship has been found to be one of the most important resources as experienced by the parents of multiples [8] and both family care workers and parents felt it was important to talk about the relationship [9,31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Systematic review shows that that parents of multiples experience heightened symptoms of depression, anxiety, and parental stress that parents of singletons. Major depression occurs in one-third of pregnant women expecting twins and is associated with higher levels of stress and lack of social support [39]. The couple's relationship has been found to be one of the most important resources as experienced by the parents of multiples [8] and both family care workers and parents felt it was important to talk about the relationship [9,31].…”
Section: Discussionmentioning
confidence: 99%
“…She described the situation in terms of themes such as power drain, pausing one's own life, striving to relax, and resuming one's own life. Major depression occurs in one-third of pregnant women expecting twins [39]. Such mothers have been shown to have significantly higher levels of parenting stress and depression than mothers of singletons, and were significantly more likely to find parenting difficult and significantly less likely to obtain pleasure from their child [40,41].…”
Section: Introductionmentioning
confidence: 99%
“…Different researches tried to evaluate the association between the presence of mood disorders and stress in parents and twin pregnancies. Researchers that focused on parental experience associated to twin pregnancy that occurs both naturally or with ART investigated either the joint experience of mothers and fathers [9][10][11][12] or of mothers alone [13][14][15][16]. It was observed that the risks usually associated to twin pregnancy lead to higher level of stress [17] and seemed to increase the incidence of depression and anxiety in parents of twins and especially in mothers [6, 9-11, 16, 18].…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that the risks usually associated to twin pregnancy lead to higher level of stress [17] and seemed to increase the incidence of depression and anxiety in parents of twins and especially in mothers [6, 9-11, 16, 18]. In addition, it was also observed that the presence of medical risk as well as psychological suffering in mothers during twin pregnancy is generally associated to higher level of fatigue, loss of energy, depressed mood and feelings of worthlessness and guilt [14].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, stress generated to parents due to the emotional, economic and social impact that entails a sudden increase in the family size must be considered (Benute et al, 2013; Ellison & Hall, 2003). …”
Section: Introductionmentioning
confidence: 99%